(3GdeRGQ GdfScis - (3GdTgjO GdChd , eMeO Hf ecj Hf eMeO Hf MGeO GdYGedj GdfHWj GdLRjfj, TeS GdOjf,J (B786 (3g` s ((3eMeO Hf WGgQ GdSeGhi s)
(3ChdgG (B:s
(3Ce HYO agPG GdefJNH ehVhY dHjGf eG jfHZi Cf jYed ai GdeTGgO GdebOSI s
(3BNQgG (B:s
(3hGdCNP HKCQge ef GdYUGHI GdedYhfI GdaGLQI s
(3HChdg agQSs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B109 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B47s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3abg GdePGgH GdCNQis